Finding Sonnet 44 in the Hécatombe à Diane: Aubigné’s Manuscripts, Revisions, and a Missing Poem - Buehrer, Sophia (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2022)
By giving no clear indication of which poem should occupy the position of the forty-fourth sonnet in his Hécatombe à Diane, Agrippa d’Aubigné left the question unanswered within the two manuscripts that contain it. Through a philological survey of these two manuscripts, this article analyzes the marginal notes and textual clues left behind in order to determine a possible choice out of several options. Such analysis of the manuscripts also makes clear that Aubigné continued to work on the Hécatombe throughout his life, and even up to the years close to his death, despite referring to these poems as youthful folly in Les Tragiques. While the question of sonnet 44 may be resolved through analysis that cannot be confirmed by the author’s notes, it makes clear that despite the rhetoric present in Les Tragiques, Aubigné continued to intentionally revise the Hécatombe à Diane well past its youthful inception.